Socialization of Ecobrick Making to Housewives in Suka Makmur Village, Gerung District, West Lombok Regency - Sri Wahyuningsih; Nurhidayah Nurhidayah; Enida Fatmalia; Dini Yuliansari; Ahmad Ruhardi (PT. Marosk Zada Cemerlang, 2022)
One of the processes for recycling waste that is environmentally friendly and does not cost a lot of money is the Ecobrick Program. Ecobricks are the use of environmentally friendly plastic waste that is used as a variety of useful items such as chairs and tables. The lack of socialization to the community about the process of making ecobricks is one of the factors that support the lack of public interest in making ecobricks. This community service program aims to provide socialization about ecobricks to the people of the Suka Makmur Village, Gerung District, West Lombok Regency. The method used in this service is in the form of training, where residents are given socialization about making ecobricks and immediately practice it. The socialization activity which was attended by the majority of mothers went smoothly. The socialization participants were enthusiastic about participating in the activity and motivated to apply the knowledge they had learned in their daily lives.